2018
DOI: 10.1186/s12967-018-1391-0
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of preoperative prognostic nutritional index in patients with hypopharyngeal squamous cell carcinoma: a retrospective study

Abstract: BackgroundTo analyze the prognostic value of preoperative prognostic nutritional index (PNI) in predicting the survival outcome of hypopharyngeal squamous cell carcinoma (HPSCC) patients receiving radical surgery.MethodsFrom March 2006 to August 2016, 123 eligible HPSCC patients were reviewed. The preoperative PNI was calculated as serum albumin (g/dL) × 10 + total lymphocyte count (mm−3) × 0.005. These biomarkers were measured within 2 weeks prior to surgery. The impact of preoperative PNI on overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 36 publications
3
37
1
Order By: Relevance
“…Concomitantly, we performed a multivariate analysis adjusting for tumor sites and further subgroup analysis to evaluate the correlation between tumor depth and pathological classification. Despite it was inadequately powered to demonstrate nodal classification, our study raised sufficient questions for further research to be validated in large populations, because we previously confirmed the predictive value of nodal burden for survival in HPSCC . It is recognized that the major limitation of this study was its retrospective nature from a single institution and associated biases.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Concomitantly, we performed a multivariate analysis adjusting for tumor sites and further subgroup analysis to evaluate the correlation between tumor depth and pathological classification. Despite it was inadequately powered to demonstrate nodal classification, our study raised sufficient questions for further research to be validated in large populations, because we previously confirmed the predictive value of nodal burden for survival in HPSCC . It is recognized that the major limitation of this study was its retrospective nature from a single institution and associated biases.…”
Section: Discussionmentioning
confidence: 89%
“…The incidence of initial N+ disease was previously reported to be 56.7%‐83.7% in HPSCC and 39.5%‐70% in SGSCC . However, surgical data from END have demonstrated a high risk of occult nodal metastasis of 31%‐57% in HPSCC and 10%‐18% in SGSCC .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations